Cr-Ni Alloy Electrodeposition and Comparison with Conventional Pure Cr Coating Technique - Moniruzzaman, M.; Rakib, M. M.; Matin, F. T. (Universiti Malaysia Pahang, 2012)
Cr coating is widely used as the outer surface of precision parts due to its attractive appearance and superior corrosion resistance properties. It is obtained by electrodeposition via a conventional bath with hexavalent Cr ions. This manufacturing technique has many drawbacks, such as very low efficiency and high operating temperature and it is hazardous to health. In this work, we studied a Cr-Ni alloy deposition technique and compared the alloy coating properties to those with conventional Cr coating. Sequential two-step alloy electrodeposition was also compared. We took varying concentrations of Cr, Ni and complexing agents for the electrodeposition of Cr-Ni alloy and sequential Cr-Ni alloy coating on mild steel. Operating parameters, i.e. current density and temperature, were varied to examine their effects on the coating properties. The coatings thus obtained were characterized by visual observation, corrosion test, microhardness measurement, morphology and chemical analysis. The Cr-Ni alloy coating was found to be more corrosion resistant in 5% NaCl solution and harder than the pure Cr coating obtained by conventional electrodeposition. Toxic gas was produced in a much lower extent in the alloy coating than the conventional Cr coating technique. Again, the two-step Cr-Ni alloy coating was found better in terms of corrosion resistance as well as hardness compared to the Cr-Ni alloy coating. The process was also found to be much more environmentally friendly.